The effect of sialoprotein local injection on dental anchorages for orthodontic tooth retraction in dogs - Chawshli, Omar Fawzi; Maroof, Rafah Al-; Jasim, Fadhil Y. (Zanco Journal of Medical Sciences (ZJMS), 2014)
Background and objective: Bone sialoprotein is a mineralized tissue-specific protein expressed in differentiated osteoblasts that appear to function in the initial mineralization of bone. The aim of this study was to investigate the effect of local bone sialoprotein on increasing the rate of anchorage during orthodontic tooth movement. Methods: This study used 14 dogs wearing orthodontic appliance for 40 days. They were divided equally into two groups; experimental group that injected with 0.1 µg /10µL sialoprotein around the anchoring tooth in three different time intervals, while the other control group received normal saline injection. Different clinical measurements including loss of anchorage, space closure, rotation, tipping and extrusion were done on the stone casts of each dog before and after tooth retraction. Results: Clinical measurements revealed a highly significant difference between experimental and control group regarding loss of anchorage and space closure. The sialoprotein injected group showed less loss of anchorage than control group and the space closure was higher in experimental group than in the control group. Conclusion: This study showed that the local injection of sialoiprotein reduced movement of the anchoring tooth during orthodontic treatment and provided higher stability for the anchoring tooth.